2013
DOI: 10.1111/j.1813-6982.2012.01326.x
|View full text |Cite
|
Sign up to set email alerts
|

Purchasing Power Parity in African Countries: Further Evidence From Fourier Unit Root Tests Based on Linear and Nonlinear Models

Abstract: This paper examines the validity of purchasing power parity hypothesis for 33 African countries using recently developed Fourier unit root tests by Christopoulos and León‐Ledesma that account for the existence of multiple breaks in the real exchange rates. The results support the evidence of the PPP in 20 countries, showing that most of the real exchange rates in the selected countries are characterised by linear or nonlinear stationary around multiple temporary mean changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 48 publications
1
9
0
2
Order By: Relevance
“…In this study, we utilize Fourier function with ADF and Fourier function with Kapetanios et al (2003) unit root tests which are the expansion of the periodic y t functions as the sum form of trigonometric terms. Fourier form unit root tests developed by Christopoulos and Leon-Ledesma (2010) allow for temporary smooth breaks by employing trigonometric variables to capture large changes in the deterministic trend (Yılancı and Eris, 2013). The initial model of the Fourier test is as follows:…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we utilize Fourier function with ADF and Fourier function with Kapetanios et al (2003) unit root tests which are the expansion of the periodic y t functions as the sum form of trigonometric terms. Fourier form unit root tests developed by Christopoulos and Leon-Ledesma (2010) allow for temporary smooth breaks by employing trigonometric variables to capture large changes in the deterministic trend (Yılancı and Eris, 2013). The initial model of the Fourier test is as follows:…”
Section: Methodsmentioning
confidence: 99%
“…A similar outcome was also observed by Chang, Lu, Tang, and Liu (2011) who incorporated asymmetric adjustment and nonlinearity into testing procedure. The success rate was further increased to 60 per cent when Yilanci and Eris (2013) considered nonlinear unit root tests and allowed multiple structural breaks using Fourier expansion. Stationarity of the real bilateral exchange rates was supported in 20 out of 33 African countries.…”
Section: The Ppp Literature In Africamentioning
confidence: 99%
“…However, it was also observed that the majority of studies reported that PPP is holds. Some of these studies are as follows: Kugler and Lenz (1993), Coakley and Fuertes (1997), Sarno (2000), Erlat (2003), Narayan (2005), Hoarau (2007), Kargbo (2009), Güloğlu et al (2011), Özcan (2012), Ağayev (2013), Yılancı and Eriş. (2013), Li et al (2015), Yalçınkaya (2016), and Aliyeva and Hüseynov (2017).…”
Section: Theoretical Framework and Related Literaturementioning
confidence: 99%